HEMATOLOGICAL CHARACTERIZATION OF BETA-THALASSEMIA IN SUDANESE PATIENTS - ELSHAIKH, RABAB HASSAN; HUSSEIN, SANAA ELFATIH (Innovare Journal of Medical Sciences, 2020)
Thalassemia is common inherited disorder among humans, and they represent a major public health problem in many areas of the world. The study aimed to the measurement of hematological characterization of beta-thalassemia in Sudanese patients. Blood samples from 61 beta-thalassemic patients were collected after written consent form obtained from all participants. The frequency of adults (>18 years) was 45 (73.8%) and children’s (<18 years) was 16 (26.2%); the frequency of male was 27 (44.3%) and 34 were female (55.7%). Hemoglobin estimation and red cell indices were carried out using the automatic blood cell counter Sysmex K × 21N. The results showed that Hb and RBCs indices were varied between mild to moderate and severe decreasing, hemoglobin concentration (Hb) with the mean value of 9.6 g/dL, with minimum value of 6.1 g/dl and maximum of 11.9 g/dl, while RBCs were increased in all patients, mean value 5.2 c/l, mean corpuscular volume mean was 58.9 fl, hematocrit was 30.4, mean corpuscular hemoglobin (MCH) 18.8 pg, mean corpuscular hemoglobin concentration (MCHC) was 31.7pg, and RDW was 18.8%. The method used for hemoglobin electrophoresis was capillary electrophoresis, Hb pattern shows increased HbA2 and HbF, the mean of HbA is 78.3%, HbF is 2.3%, and HbA2 is 6.5% with the min. value of 3.6% and max. of 12.2%. While the mean of serum iron was 82.75 μg/dl, 7 patients showed low level, 19 high level, and 35 were normal level. Comparison of hematological analysis (HbA2) in thalassemic patients coexisted with iron deficiency and without result was insignificant difference (p=0.645), this result disagrees with references that say iron deficiency masking HbA2. Nevertheless, the association between HbA2 and HbF revealed a statistically significant difference (p<0.013) and HbA2 with Hb was insignificant (p=0.260).